CRISPR/Cas9 Genome Editing Introduction and Optimization in the Non-model Insect Pyrrhocoris apterus - Kotwica-Rolinska, Joanna; Chodakova, Lenka; Chvalova, Daniela; Kristofova, Lucie; Fenclova, Iva; Provaznik, Jan; Bertolutti, Maly; Wu, Bulah Chia-Hsiang; Dolezel, David (Frontiers in Physiology, 2019)
The CRISPR/Cas9 technique is widely used in experimentation with human cell lines as well as with other model systems, such as mice Mus musculus, zebrafish Danio reiro, and the fruit fly Drosophila melanogaster. However, publications describing the use of CRISPR/Cas9 for genome editing in non-model organisms, including non-model insects, are scarce. The introduction of this relatively new method presents many problems even for experienced researchers, especially with the lack of procedures to tackle issues concerning the efficiency of mutant generation. Here we present a protocol for efficient genome editing in the non-model insect species Pyrrhocoris apterus. We collected data from several independent trials that targeted several genes using the CRISPR/Cas9 system and determined that several crucial optimization steps led to a remarkably increased efficiency of mutant production. The main steps are as follows: the timing of embryo injection, the use of the heteroduplex mobility assay as a screening method, in vivo testing of sgRNA efficiency, and G0 germline mosaicism screening. The timing and the method of egg injections used here need to be optimized for other species, but other here-described optimization solutions can be applied immediately for genome editing in other insect species.